O'Brien, Aloysius 10. Interview about different insect pests in the field - Shawyer; Jo (1992)
The topics concentrate on the insect pests and some ways against them. Aloysius also mentioned the selling of turnip greens. 00:00 – 07:25 flea beetle; turnip flies; culch worms; insect pests; turnip greens for sell